2015
DOI: 10.1186/s12888-014-0380-y
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of psychiatric hospital staff toward hospitalization and treatment of patients with borderline personality disorder

Abstract: BackgroundNegative attitudes towards patients with borderline personality disorder (BPD) may affect their treatment. We aimed to identify attitudes toward patients with BPD.MethodsClinicians in four psychiatric hospitals in Israel (n = 710; psychiatrists, psychologists, social workers and nurses) were approached and completed questionnaires on attitudes toward these patients.ResultsNurses and psychiatrists reported encountering a higher number of patients with BPD during the last month, and exhibited more nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
138
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(154 citation statements)
references
References 43 publications
10
138
3
1
Order By: Relevance
“…Researchers and clinicians should always be wary of the potential harmful effects of diagnostic labeling. PD generally-and borderline and antisocial (including psychopathy) PD more specifically-are stigmatized among some mental health professionals, patients, the judicial system, and society at large (244)(245)(246)(247). However, well-intentioned clinicians who purposefully refrain from using PD diagnoses with adolescent patients in order to avoid stigma or discrimination may thereby unwittingly be reinforcing and perpetuating the very stigma that they wish to avoid (170).…”
Section: Hume's Guillotine: Barriers and Potential Risksmentioning
confidence: 99%
“…Researchers and clinicians should always be wary of the potential harmful effects of diagnostic labeling. PD generally-and borderline and antisocial (including psychopathy) PD more specifically-are stigmatized among some mental health professionals, patients, the judicial system, and society at large (244)(245)(246)(247). However, well-intentioned clinicians who purposefully refrain from using PD diagnoses with adolescent patients in order to avoid stigma or discrimination may thereby unwittingly be reinforcing and perpetuating the very stigma that they wish to avoid (170).…”
Section: Hume's Guillotine: Barriers and Potential Risksmentioning
confidence: 99%
“…It is important to systematically appraise and synthesise the available evidence as some studies (Bodner et al . , ) have concluded that mental health nurses hold the poorest attitudes of all professional groups. We have recently conducted a systematic review of interventions that aimed to improve the attitudes and/or behaviour of groups of clinicians, including mental health nurses, towards people diagnosed with borderline personality disorder (Dickens et al .…”
Section: Introductionmentioning
confidence: 99%
“…Managing patients with personality disorders begins by recognizing that these individuals evoke strong responses from even the most seasoned professional . Reactions toward people with personality disorders can range from a need to care for and protect the patient to feelings of futility or contempt .…”
Section: Behavioral Interventionsmentioning
confidence: 99%